2020
DOI: 10.1370/afm.2555
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers to and Facilitators of Case Management in Primary Care: A Systematic Review and Thematic Synthesis

Abstract: PURPOSE Despite evidence on the benefits of case management for the care of patients with complex needs in primary care, implementing the program-necessary to achieve its benefits-has been challenging worldwide. Evidence on factors affecting implementation remains disparate. Accordingly, the objective of this systematic review was to identify barriers to and facilitators of case management, from the perspectives of health care professionals, in primary care settings around the world. METHODSWe conducted a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 70 publications
(135 reference statements)
3
13
0
3
Order By: Relevance
“…It has a good effect on expanding the strength of the breathing and lung-related muscles and improving the following the law/doing as you are told of the lungs and small tube (from the mouth to the lungs), which in turn has a positive effect on improving the quality of life of the patients [ 25 ]. Some studies have shown that patients with lung scale-like cell cancer are much more depressed than ordinary people and have a heavier self-perceived heavy load, which seriously affects the treatment of the disease and the quality of life of patients [ 26 ]. Self-perceived heavy load includes patients' concerns about their need to depend on others for physical care, worry about the emotional hit/effect of their illness and death on their family members, and concerns about important role responsibilities and responsibilities that cannot be satisfied [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a good effect on expanding the strength of the breathing and lung-related muscles and improving the following the law/doing as you are told of the lungs and small tube (from the mouth to the lungs), which in turn has a positive effect on improving the quality of life of the patients [ 25 ]. Some studies have shown that patients with lung scale-like cell cancer are much more depressed than ordinary people and have a heavier self-perceived heavy load, which seriously affects the treatment of the disease and the quality of life of patients [ 26 ]. Self-perceived heavy load includes patients' concerns about their need to depend on others for physical care, worry about the emotional hit/effect of their illness and death on their family members, and concerns about important role responsibilities and responsibilities that cannot be satisfied [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Malebranche et al recently suggested that further research was needed to better understand the advantages and disadvantages of implementing case management as primary care program versus predominantly ED or hospital-based one [42]. Teper et al's systematic review of CMP implementation in primary care settings identified common facilitators and barriers of CMP implementation in hospital settings including case managers' skills, training, and relationship building and team communication practices [43]. In a systematic mixed studies review on the barriers of CMP implementation for people with dementia in community-based primary health care, Khanassov et al also reported the importance of communication between case managers and other professionals and services [44].…”
mentioning
confidence: 99%
“…48 Our finding that high-integration H-PACTs were associated with more favorable access/coordination experiences may have service design implications, particularly as it relates to implementing case management in primary care. 49,50 From its inception, H-PACT was described as a one-stop model of care, where multiple and sometimes competing needs could be addressed in a single setting. 51 Our data suggest that PEH with SMI who receive primary care in "one-stop shops" with highly integrated services 52 -extending beyond the basics of primary caremental health integration 53 to encompass social services-may have better care experiences.…”
Section: Discussionmentioning
confidence: 99%